Radiographic evaluation of third molar development in 5- to 25 year olds in tehran, iran. - A Jafari; Sz Mohebbi; Mr Khami; M Shakur Shahabi; M Naseh; F Elhami; Ar Shamshiri (Tehran University of Medical Sciences, 2012)
Radiographic evaluation of the third molar tooth to determine its position and degree of development is an important part in diagnosis and treatment planning, as well as in forensic dentistry procedures. The objective was to investigate the developmental stages of third molars in relation to chronologic age, gender and location (maxillary/mandibular) in an Iranian population.The data were collected in departments of pediatric dentistry and orthodontics, Tehran Faculty of Dentistry and four private offices. Three calibrated observers visited the centers to examine panoramic radiographs and corresponded patients documents in each age cohort in the range of 5- to-25-years old. Data were analyzed by Generalized Estimating Equation (GEE) in the linear mode and exchangeable correlation structure. The significance level was defined as 0.05.The mean age of emerging third molars' follicle was 9.29±1.65 years. Early calcification was seen at the mean age of 10.28±1.66 years. The GEE model controlling for age, gender and tooth location (maxillary/mandibular) revealed that besides age (β=0.43, p